EFFECT OF MICRO-ENTREPRENEURSHIP ON HOUSEHOLD POVERTY LEVEL: EVIDENCE FROM NIGERIA - Kamaldeen Ibraheem Nageri (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2024)
Nigeria's high rates of poverty, unemployment, and poor income continue to be a major cause of worry. Despite the implementation of various entrepreneurial efforts by government and non-governmental organizations, income remains low, which is exacerbated by the country's high percentage of young unemployment. While previous research has looked at the function of entrepreneurship in raising welfare and boosting shared prosperity, the intervening role of income in these relationships has gotten less attention, especially in the context of primary data analysis. This prompted this study to examine the impact of micro-entrepreneurship on income generation in the Ilorin, as a case study. During the investigation, data was collected at random from 430 entrepreneurs. Using cross-tabulation and the chi-square statistic. The researchers discovered a positive but inconsequential relationship between micro-entrepreneurship and revenue production. This may be explained by the fact that 42% of the 291 entrepreneurs that are regarded innovators have a modest income. The findings of this research show that when the government provides appropriate financing to stimulate entrepreneurship and the inventive spirit, it generates more income and helps to reduce poverty. The study provides data to corroborate the literature, emphasizing the favorable impact of appropriate entrepreneurial funding on revenue growth. It was shown that most of the entrepreneurs surveyed focused on the issue of insufficient funding. This has constrained entrepreneurs' creativity and innovation, forcing them to operate on a small scale with minimal profits.